Principles and practice to facilitate complete photodocumentation of the upper gastrointestinal tract: World Endoscopy Organization position statement. Issue 2 (6th November 2019) - Emura, Fabian; Sharma, Prateek; Arantes, Vitor; Cerisoli, Cecilio; Parra‐Blanco, Adolfo; Sumiyama, Kazuki; Araya, Raul; Sobrino, Sergio; Chiu, Philip; Matsuda, Koji; Gonzalez, Robinson; Fujishiro, Mitsuhiro; et al.
Abstract : Although esophagogastroduodenoscopy (EGD) is the most commonly used procedure in the gastrointestinal (GI) tract, the method of esophageal, gastric and duodenal mucosa photodocumentation varies considerably worldwide. One probable explanation is that for generations, EGD has primarily been taught by GI faculty and instructors based on their perceptions and experience, which has resulted in EGD being a non‐standardized procedure. Currently, the procedure is facing a challenging scenario as endoscopy societies are implementing procedure‐associated quality indicators aiming for best practice among practitioners and evidence‐based care for patients. Contrary to colonoscopy where cecum landmarks photodocumentation is considered proof of completeness, there are currently no reliable performance measures to gauge the completeness of an upper endoscopy nor guidance for complete photodocumentation. This World Endoscopy Organization (WEO) position statement aims to provide practical guidance to practitioners to carry out complete EGD photodocumentation. Hence, an international group of experts from the WEO Upper GI Cancer Committee formulated the following document using the body of evidence established through literature reviews, expert opinions, and other scientific sources. The group acknowledged that although the procedure should be feasible in any facility, what is needed to achieve a global shift on the concept of completeness is a common written statement of agreement on its potential impact and added value. This best practice statement offers endoscopists principles and practical guidance in order to carry out complete photodocumentation from the hypopharynx to the second duodenal portion.